Isostasy and Seismicity of the East Asia Transitional Zone (Izostaziya i Seismichnost Vostochno-Aziatskoi Perekhodnoi Zony) - Pavlov,Yu. A.; Semakin,V. P. (1974)
The problems discussed in the present work concern the isostatic condition of the earth's crust and the spatial distribution of earthquake hypocenters in the region which covers the water areas of the marginal seas of the Far East and the adjacent part of the Pacific Ocean, as well as the border land of the Asian continent towards the Pacific Ocean. Technical trans. from mono. Izostaziya (Isostasy) Moscow, 1973 p105-121, by Henry Tomas.